2011
DOI: 10.2174/138620711794474088
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Polarity on the Scalability and Reproducibility of Solvent-Free Microwave-Assisted Reactions

Abstract: Organic reactions performed in the absence of solvent in domestic ovens without appropriate temperature control are generally considered as not reproducible, particularly when different instruments are used. For this reason, reproducibility has historically been one of the major issues associated with Microwave-Assisted Organic Synthesis (MAOS) especially when domestic ovens are involved. The lack of reproducibility limits the general applicability and the scale up of these reactions. In this work several solv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
2
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…Similar conclusions were reported by Leadbeater in a study into the rapid optimization of reaction conditions (Leadbeater & Schmink, 2007). In order to extend the preliminary results to see whether any solvent-free reaction previously performed in a domestic oven can be reproduced in dedicated apparatus, the same authors studied four new reactions that cover a wide range of chemical transformations (Díaz-Ortiz et al, 2011). It was found that N-alkylation of (1H)-benzotriazoles, condensation of anilines with urea (or thiourea) and Beckmann rearrangement of ketoximes are reproducible in both single-mode and multimode microwave instruments using temperature-controlled conditions.…”
Section: Reproducibility Across Instrumentssupporting
confidence: 61%
“…Similar conclusions were reported by Leadbeater in a study into the rapid optimization of reaction conditions (Leadbeater & Schmink, 2007). In order to extend the preliminary results to see whether any solvent-free reaction previously performed in a domestic oven can be reproduced in dedicated apparatus, the same authors studied four new reactions that cover a wide range of chemical transformations (Díaz-Ortiz et al, 2011). It was found that N-alkylation of (1H)-benzotriazoles, condensation of anilines with urea (or thiourea) and Beckmann rearrangement of ketoximes are reproducible in both single-mode and multimode microwave instruments using temperature-controlled conditions.…”
Section: Reproducibility Across Instrumentssupporting
confidence: 61%
“…73 In the first case, the Finally, Díaz-Ortiz and col. reinvestigated five solvent-free reactions previously carried out in domestic ovens, with the aim of demonstrating the reproducibility and scalability of solventfree reactions. 74 The authors translated the reactions into a single-mode microwave reactor and then scaled them up in a multimode oven. The results show that most of these reactions can be easily scaled in microwave reactors using temperaturecontrolled conditions.…”
Section: Evolution Of Polarity Along the Reaction Pathmentioning
confidence: 99%
“…More recently, more extended computational calculations were shown to represent a very useful tool to study separately the occurrence of the thermal and nonthermal effects of MW irradiation through the determination of the thermodynamic and kinetic parameters of the reactions [84,85] (see also Chapter 6 dedicated to this point).…”
Section: Effects Depending On Reaction Mechanismsmentioning
confidence: 99%
“…Such an assumption was verified experimentally and justified by considering theoretical calculations predicting an asynchronous mechanism in the cycloaddition of N-methylazomethine ylide to C 70 fullerene [61]: This reaction was examined by computational calculations to assess the effect of MW irradiation. It was concluded that the thermodynamic product would be favored under MW exposure, indicating the presence of only thermal effects at higher temperatures [85].…”
Section: Isopolar Transition-state Reactionsmentioning
confidence: 99%